Contrast-induced encephalopathy: a complication of coronary angiography. Issue 6 (28th August 2020) - Fernando, Tharanga Geethapriya; Nandasiri, Shanika; Mendis, Sepalika; Senanayake, Sunethra; Gooneratne, Inuka Kishara; Navinan, Rayno; Kadiragamanathan, Ambiga; Wickramasinghe, Sumudu; Herath, Tharuka; Thambirajah, Narmathey; Markus, Romesh
Abstract : Contrast-induced encephalopathy is a rare idiosyncratic reaction to contrast material. A 56-year-old woman with hypertension developed a hemiparesis with confusion and disorientation 3 hours after routine coronary angiography. The procedure had been prolonged, and during it she had received 130 mL of iopromide contrast. A metabolic screen was negative, and cerebral angiography and MR scan of brain were normal. She recovered completely by day 5. Contrast-induced encephalopathy should be considered in patients developing focal neurological deficits following coronary angiography. Patients requiring investigations to exclude acute stroke in this setting should not receive additional intravenous or intra-arterial contrast, although MR with gadolinium appears safe. Better awareness of this complication should avoid potentially harmful interventions such as thrombolysis.